Surgical and Non-Surgical Treatment Outcome Assessed by Voice Handicap Index of Patients with Vocal Fold Nodule - Palash, Chirangib Singha; Uddin, Md Mosleh; Salam, Kazi Shameemus; Ahmad, SM Mesbah Uddin; Sayied, Md Jaber Al; Haque, Md Hasanul (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Vocal nodules are a frequently occurring type of laryngeal disorder. Vocal fold nodules are usually bilateral swellings of variable size (< 3mm) found at the mid-part of the membranous vocal cords. Vocal abuse, misuse and overuse are frequently claimed to be the causes of vocal nodules and mostly affect professional voice users. It has important public health implications and impact on patient quality of life (QoL). Voice handicap index (VHI) is an important tool for quality of life assessment and outcome of intervention in voice disordered patients. Objective: To compare the outcome of Voice handicap index (VHI) score after surgical and non-surgical intervention of vocal cord nodule. Methods: In this prospective study 30 patients with vocal nodules refractory to the first session of voice therapy were diagnosed by fiber optic laryngoscopy. After simple random allocation management was done either by voice therapy or surgery. VHI (Voice Handicap Index) was applied as outcome measures for assessing the efficiency of intervention between surgical and non-surgical groups. Results: The mean value of Voice handicap index total (VHIt) was 54.40 (± 8.56) before voice therapy which significantly changed to 25.80 (± 6.23) after voice therapy in non-surgical group(n2). Bangladesh J Otorhinolaryngol 2022; 28(1): 29-36